Promosi Lagu “Takut” di Media Sosial Tiktok - Roro Aulia Arsyta Fajriyanti; Mariana Rista Ananda Siregar; Qoute Nuraini Cahyaningrum (Jurnal Penelitian Sosial Ilmu Komunikasi, 2024)
The purpose of this study is to understand how the marketing public relations of the song "Takut" by Idgitaf on the TikTok application works and the effectiveness of TikTok as a marketing public relations medium for the song "Takut" by Idgitaf. The research method used is descriptive qualitative. Data sources were obtained through in-depth analysis and interviews. Interviews were conducted with Idgitaf the singer of the song "Takut", Idgitaf's manager, fans, and a social media specialist/content specialist from DANA. The results of the study show that Idgitaf carries out marketing communication or more specifically marketing public relations in promoting the song "Takut" on the TikTok social media platform. In marketing and promotional activities, Idgitaf employs three strategic techniques. Firstly, Idgitaf uses a pull strategy by creating relevant promotional videos or content that resonates with its target market segment. Secondly, Idgitaf utilizes a push strategy by creating massive and varied videos or content to market the song "Takut". Thirdly, Idgitaf employs a passing strategy by consistently promoting the song even after it has gained popularity in the market. This is done to maintain the song's presence. TikTok also proves to be an effective promotional medium as the marketing and promotion efforts conducted significantly impact the success of the song "Takut".